A MUCINs expression signature impacts overall survival in patients with clear cell renal cell carcinoma. (29th July 2021) - Meng, Hui; Jiang, Xuewen; Huang, Huangwei; Shen, Neng; Guo, Changsheng; Yu, Chunxiao; Yin, Gang; Wang, Yu
Abstract: Background: Kidney cancer, especially clear cell renal cell carcinoma (ccRCC), is one of the most common cancers in the urinary system. Previous studies suggested that certain members of MUCIN s could serve as independent predictors for the survival of ccRCC patients. None of them, however, is robust enough to predict prognosis accurately. Objective: To analyze the correlation of MUCINs alterations and their expression levels with the prognosis of ccRCC patients and develop a prognosis‐related predictor. Methods: We applied whole‐exome sequencing in samples from 22 Chinese ccRCC patients to identify genetic alterations in MUCIN genes and analyzed their genetic alterations, expression, and correlation with survival using the TCGA, GSE73731, and GSE29069 datasets. Result: Genetic alternations in MUCINs were identified in 91% and 51% of ccRCC patients in our cohort and the TCGA database, respectively. No correlation with survival was found for the genetic alterations. Using unsupervised clustering analysis of gene expression, we identified two major clusters of MUCIN expression patterns. Cluster 1 was characterized by a global overexpression of MUC1, MUC12, MUC13, MUC16, and OVGP1 ; and cluster 2 was characterized by a global overexpression of MUC4, MUC5B, MUC6, MUC20, EMCN, and MCAM . Patients with cluster 1 expression pattern had significantly shorter overall survival time and worse clinical features, including higher tumor grades and metastasis. Meanwhile, they had a higher level of mutation counts and more infiltrated immune cells, but lower enrichment in angiogenesis signature genes. A five‐ MUCINs expression signature was constructed from cluster 1, and notably, it was demonstrated to be associated with shorter overall survival. A similar worse clinical feature, lower angiogenesis but the more immune signature, was identified in samples presented with signature 1. In the validation data set GSE29069, patients with signature 1 were also associated with a trend of poor survival outcomes. Conclusion: We established a five‐ MUCINs expression signature as a new prognostic marker for ccRCC. The distinct tumor microenvironment feature between the two signatures may further affect ccRCC patients' clinical management. Abstract : We identified a five‐MUCINs expression signature associated with the prognosis for ccRCC patients, which provided a new prognostic marker for ccRCC patients. The distinct tumor microenvironment feature between the two signatures may further affect ccRCC patients' management.